Fluorine-containing titanium oxide nanoparticle photoresist material, preparation method thereof and application of fluorine-containing titanium oxide nanoparticle photoresist material in photoetching technology

By introducing fluorine-containing titanium oxide nanoparticles into the photoresist, the problems of instability and poor solubility of existing titanium-based photoresist are solved, and high thermal stability and high resolution imaging capabilities are achieved, suitable for electron beams and ultraviolet light Engraving technology.

CN119414657APending Publication Date: 2025-02-11SHANDONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411478417.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Due to instability, poor solubility and poor film formation quality, existing titanium-based photoresist cannot achieve photolithographic imaging with high resolution and low line width roughness.

Method used

The nanoparticle photoresist material is used to react the fluorine-containing ligand with the titanium source in a solvent to form a nanoparticle photoresist, which improves its thermal stability, solubility and film formation quality.

Benefits of technology

It has achieved high thermal stability, improved solubility and film formation quality, high adhesion performance and high resolution imaging capabilities, and can achieve high resolution patterning characteristics of 12nm line width in electron beam lithography and ultraviolet lithography. Low line width roughness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005096697970000091
    Figure BDA0005096697970000091
  • Figure BDA0005096697970000092
    Figure BDA0005096697970000092
  • Figure HDA0005096697980000011
    Figure HDA0005096697980000011
Patent Text Reader

Abstract

The invention provides a fluorine-containing titanium oxide nanoparticle photoresist material, a preparation method thereof and an application of the fluorine-containing titanium oxide nanoparticle photoresist material in a photoetching technology. The preparation method of the fluorine-containing titanium oxide nanoparticle photoresist material comprises the following steps: dissolving a fluorine-containing ligand and a fluorine-free ligand in a solvent A to obtain a solution A; dissolving a titanium source in a solvent B to obtain a solution B; and fully and uniformly mixing the solution A and the solution B, carrying out solvothermal reaction, and then filtering, washing and drying to obtain the fluorine-containing titanium oxide nanoparticle photoresist material. The preparation method of the photoresist material is simple and suitable for industrial production; the obtained photoresist material has the advantages of high thermal stability, relatively good solubility and film forming quality, good substrate adhesion performance and the like; the method is used for the electron beam lithography technology, shows high-resolution imaging capability and low line width roughness, and has wide application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of photolithography materials, and in particular to a fluorine-containing titanium oxide nanoparticle photoresist material and a preparation method thereof and application in photolithography technology. Background Art

[0002] Photolithography is a micro-nano processing technology that is widely used in integrated circuit manufacturing, flat panel display manufacturing and other fields. In photolithography, photoresist materials play a vital role. Photoresist is an indispensable material for photolithography in semiconductors. At present, the main chemically amplified photoresist that has been commercialized is composed of polymers and photoacids, and has always been the main force in the integrated circuit manufacturing industry. However, due to the large hydrodynamics or gyration radius of the polymer in the chemically amplified photoresist, the random effects associated with the acid diffusion process, and the poor etching resistance, it is difficult to achieve low line width roughness (LWR) and etching resistance patterning. With the development of science and technology and the growth of market demand, higher requirements are placed on photolithography and photoresist materials. In the semiconductor industry, the requirements for chip size and density are getting higher and higher, which requires better photoresist materials to achieve.

[0003] Metal oxide nanoparticle photoresists modified by organic ligands are a promising type of photolithographic material and have attracted widespread attention. Compared with polymer-based photoresists, metal oxide photoresists have a larger extreme ultraviolet light absorption cross section, smaller molecular size, and higher etching resistance. They can provide better patterning resolution, lower line edge roughness, and better etching resistance, and are the most promising candidates in photoresists.

[0004] Due to the instability, poor solubility and poor film quality of titanium-based materials, research on titanium-based photoresists has mostly focused on using UV-sensitive chelating agents to stabilize titanium alkoxide compounds and using heterogeneous metal mixed photoresists such as titanium-zinc-based (Wang D, Xu R, Zhou D, et al. Zn-Ti oxo cluster photoresists for EUV Lithography: Cluster structure and lithographic performance[J]. Chemical Engineering Journal, 2024, 493: 152315.) and titanium-zirconium-based (Qiao Y, Shi G, Zhang O, et al. Heterometallic Ti-Zr oxonanocluster photoresists for advanced lithography[J]. Science China Materials, 2024: 1-10.) for nanostructure manufacturing. However, although some people have found that titanium oxide nanoparticle photoresists modified with methacrylic acid as ligands can achieve 300nm lines under DUV (Stehlin F, Wieder F, Spangenberg A, et al. Room-temperature preparation of metal-oxide nanostructures by DUV lithography from metal-oxo clusters [J]. Journal of Materials Chemistry C, 2014, 2 (2): 277-285.), it is still a challenge for single-component titanium-based nanoparticle photoresists to achieve sub-20nm high resolution.

[0005] Therefore, it is of great significance to develop a photoresist material with high thermal stability, improved solubility and film quality, high adhesion to the substrate, and high-resolution imaging. Summary of the invention

[0006] The present invention aims to overcome the limitation of photoresist types, solve the problems that the existing titanium-based photoresist cannot be used for photolithography application imaging due to poor film quality caused by instability and poor solubility, and the imaging resolution needs to be further improved. The present invention provides a fluorine-containing titanium oxide nanoparticle photoresist material and its preparation method and application in photolithography technology. The photoresist material preparation method of the present invention is simple and suitable for industrial production; the obtained photoresist material has the advantages of high thermal stability, good solubility and film quality, good adhesion to the substrate, etc.; it is used in electron beam lithography technology, showing the ability of high-resolution imaging and low line width roughness, and has a wide range of application value.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing a fluorine-containing titanium oxide nanoparticle photoresist material comprises the following steps:

[0009] (1) dissolving a fluorine-containing ligand and a non-fluorine-containing ligand in a solvent A to obtain a solution A;

[0010] (2) dissolving a titanium source in solvent B to obtain solution B;

[0011] (3) Solution A and solution B are fully mixed, subjected to solvent thermal reaction, and then filtered, washed, and dried to obtain a fluorine-containing titanium oxide nanoparticle photoresist material.

[0012] According to the preferred embodiment of the present invention, in step (1), the fluorine-containing ligand is 2-fluorobenzoic acid, 3-fluorobenzoic acid, 4-fluorobenzoic acid, 2,3-difluorobenzoic acid, 2,4-difluorobenzoic acid, 2,5-difluorobenzoic acid, 2,6-difluorobenzoic acid, 3,4-difluorobenzoic acid, 2,4,5-trifluorobenzoic acid, 2,4,6-trifluorobenzoic acid, 3-fluoro-2-(trifluoromethyl)benzoic acid, 2-fluorophenylacetic acid, 2,4,5-trifluorophenylacetic acid or 2-(trifluoromethyl)acrylic acid, or a combination of two or more thereof. Preferably, the fluorine-containing ligand is 2-fluorobenzoic acid.

[0013] Preferably according to the present invention, in step (1), the fluorine-free ligand is one or a combination of two or more of benzoic acid, 2-methylbenzoic acid, 3-methylbenzoic acid, 4-methylbenzoic acid, 4-aminobenzoic acid, 4-hydroxybenzoic acid, 2-methylphenylacetic acid, 3-methylphenylacetic acid, 4-methylphenylacetic acid or methacrylic acid.

[0014] Preferably according to the present invention, in step (1), the molar ratio of the fluorine-containing ligand to the fluorine-free ligand is 1:0.5-1:4, preferably 1:1-1:3.6.

[0015] Preferably, in step (1), solvent A is one of acetonitrile, ethyl acetate, n-hexane or n-heptane; and the volume ratio of the molar amount of the fluorinated ligand to solvent A is 0.1-0.5 mol / L.

[0016] Preferably according to the present invention, in step (2), the titanium source is one of isopropyl titanate or tetrabutyl titanate.

[0017] Preferably according to the present invention, in step (2), solvent B is one of acetonitrile, ethyl acetate, n-hexane or n-heptane; and the volume ratio of the titanium source to solvent B is 1:6-7.

[0018] Preferably, according to the present invention, the volume ratio of the molar amount of the fluorine-containing ligand in solution A of step (1) to the volume ratio of the titanium source in solution B of step (2) is 6-15 mol:1L.

[0019] Preferably according to the present invention, in step (3), the reaction temperature is 60-100° C. and the reaction time is 15-24 h.

[0020] A fluorine-containing titanium oxide nanoparticle photoresist material is obtained by the method.

[0021] Preferably, according to the present invention, the microscopic morphology of the fluorine-containing titanium oxide nanoparticle photoresist material is nanoparticles with a particle size of 3-11 nm.

[0022] A photoresist composition comprises the following components by weight: 50-99 parts of solvent, 1-50 parts of fluorine-containing titanium oxide nanoparticle photoresist material, and 0-10 parts of photoacid.

[0023] According to the present invention, the solvent is preferably selected from one or a combination of two or more of cyclopentanone, cyclohexanone, acetone, propylene glycol methyl ether acetate, ethyl lactate, butyl lactate, toluene, dimethyl sulfoxide or tetrahydrofuran. Preferably, the solvent is cyclopentanone.

[0024] According to the present invention, the photoacid is preferably selected from N-hydroxynaphthalimide trifluoromethanesulfonic acid (NIT), 2-(2-(((octylsulfonyl)oxy)imino)thiophene-3(2H)-ylidene)-2-(o-tolyl)acetonitrile (PAG 108) or N-hydroxyphthalimide p-toluenesulfonate.

[0025] The preparation method of the photoresist composition comprises the steps of: fully dispersing the fluorine-containing titanium oxide nanoparticle photoresist material and the photoacid in a solvent to obtain the photoresist composition.

[0026] Application of the above fluorine-containing titanium oxide nanoparticle photoresist material or photoresist composition in photolithography technology.

[0027] The technical features and beneficial effects of the present invention are as follows:

[0028] 1. The preparation method of the photoresist material of the present invention is simple, the raw materials are cheap and easily available, the cost is low, and it is suitable for industrial production.

[0029] 2. The present invention introduces fluorine-containing ligands. First, the fluorine element has a larger absorption cross-section than elements such as carbon and oxygen, which can enhance the absorbance of the photoresist, optimize the performance of the photoresist, and improve the patterning accuracy and resolution; secondly, the fluorine element has a strong electronegativity and can attract electrons to deviate toward itself, thereby affecting the electron cloud distribution and chemical properties of molecules or ions. This electronic effect can improve the hydrophobicity of the photoresist and improve the solubility and stability of the photoresist; in addition, the introduction of the fluorine element can improve the adhesion properties of the photoresist and enhance the adhesion between the photoresist and the substrate surface.

[0030] 3. The electronic effect of the fluorine-containing ligand introduced in the present invention makes the fluorine-containing titanium oxide nanoparticle photoresist material of the present invention have excellent solubility, film-forming property, high thermal stability and chemical stability, good adhesion performance to the substrate, and has application feasibility in electron beam lithography and ultraviolet lithography. Compared with fluorine-free titanium oxide nanoparticle photoresist materials, it can achieve high-resolution patterning features with a line width of 12nm and low line width roughness, and has wide application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is the H-NMR spectrum of F-BA-BA-Ti 1 / 1.35 and F-BA-BA-Ti 1 / 0.78 prepared in Example 1-2.

[0032] Figure 2 These are the H-NMR spectra of F-BA-m-TA-Ti 1 / 1.19 and F-BA-m-TA-Ti 1 / 1 prepared in Example 3-4.

[0033] Figure 3 The thermogravimetric spectra of F-BA-BA-Ti 1 / 0.78 and F-BA-m-TA-Ti 1 / 1 prepared in Examples 2 and 4 in an argon atmosphere.

[0034] Figure 4 It is the particle size analysis spectrum of F-BA-BA-Ti 1 / 1.35 and F-BA-BA-Ti 1 / 0.78 prepared in Example 1-2.

[0035] Figure 5 It is the particle size analysis spectrum of F-BA-m-TA-Ti 1 / 1.19 and F-BA-m-TA-Ti 1 / 1 prepared in Example 3-4.

[0036] Figure 6 The following are morphology images of four photoresist films prepared in Examples 6-9 under an atomic force microscope.

[0037] Figure 7 is a scanning electron microscope image of the electron beam lithography pattern of the photoresist film of Examples 6-9.

[0038] Figure 8 This is a scanning electron microscope image of the electron beam lithography pattern of the photoresist film prepared from the fluorine-free titanium oxide nanoparticle photoresist material I in Comparative Example 3.

[0039] Fig. 9 This is a scanning electron microscope image of the electron beam lithography pattern of the photoresist film prepared from the fluorine-free titanium oxide nanoparticle photoresist material II in Comparative Example 4. DETAILED DESCRIPTION

[0040] The present invention is further described below by means of specific examples, in which the raw materials are all commercially available.

[0041] It should be understood that the above embodiments are only exemplary descriptions and explanations of the present invention, and do not limit the protection scope of the present invention. The technologies implemented based on the above contents are all included in the scope of protection intended by the present invention.

[0042] Example 1

[0043] A method for preparing a fluorine-containing titanium oxide nanoparticle photoresist material comprises the following steps:

[0044] (1) 2-Fluorobenzoic acid (1.4 g, 10 mmol) and benzoic acid (4.4 g, 36 mmol) were dissolved in 51 mL of acetonitrile to form solution A;

[0045] (2) dissolving 1.6 mL of isopropyl titanate in 10.2 mL of acetonitrile to form solution B;

[0046] (3) Solution A was transferred to solution B, and the mixture was stirred evenly, then transferred to a 100 mL polytetrafluoroethylene-lined reactor and placed in an oven for solvothermal reaction. The heating temperature was set to 100 °C and the reaction time was 15 h. After the heating reaction was completed, the mixture was naturally cooled to room temperature. After filtering, washing and drying, a fluorine-containing titanium oxide nanoparticle photoresist material was obtained. According to the test results of nuclear magnetic hydrogen spectrum, the product was named F-BA-BA-Ti 1 / 1.35 according to the molar ratio of 2-fluorobenzoic acid and benzoic acid in the actual product.

[0047] Example 2

[0048] A method for preparing a fluorine-containing titanium oxide nanoparticle photoresist material comprises the following steps:

[0049] (1) 2-Fluorobenzoic acid (3.23 g, 23 mmol) and benzoic acid (2.81 g, 23 mmol) were dissolved in 51 mL of acetonitrile to form solution A;

[0050] (2) dissolving 1.6 mL of isopropyl titanate in 10.2 mL of acetonitrile to form solution B;

[0051] (3) Solution A was transferred to solution B, and the mixture was stirred evenly, and then transferred to a 100 mL polytetrafluoroethylene-lined reactor and placed in an oven for solvothermal reaction. The heating temperature was set to 100 ° C, and the reaction time was 15 h. After the heating reaction was completed, it was naturally cooled to room temperature. After filtering, washing, and drying, a fluorine-containing titanium oxide nanoparticle photoresist material was obtained. According to the test results of nuclear magnetic hydrogen spectrum, it was named F-BA-BA-Ti 1 / 0.78 according to the molar ratio of 2-fluorobenzoic acid and benzoic acid in the actual product.

[0052] Example 3

[0053] A method for preparing a fluorine-containing titanium oxide nanoparticle photoresist material comprises the following steps:

[0054] (1) 2-Fluorobenzoic acid (1.4 g, 10 mmol) and 3-methylbenzoic acid (4.87 g, 36 mmol) were dissolved in 51 mL of acetonitrile to form solution A;

[0055] (2) dissolving 1.6 mL of isopropyl titanate in 10.2 mL of acetonitrile to form solution B;

[0056] (3) Solution A was transferred to solution B, and the mixture was stirred evenly, and then transferred to a 100 mL polytetrafluoroethylene-lined reactor and placed in an oven for solvothermal reaction. The heating temperature was set to 100 °C and the reaction time was 15 h. After the heating reaction was completed, it was naturally cooled to room temperature. After filtering, washing, and drying, a fluorine-containing titanium oxide nanoparticle photoresist material was obtained. According to the test results of nuclear magnetic hydrogen spectrum, it was named F-BA-m-TA-Ti 1 / 1.19 according to the molar ratio of 2-fluorobenzoic acid and 3-methylbenzoic acid in the actual product.

[0057] Example 4

[0058] A method for preparing a fluorine-containing titanium oxide nanoparticle photoresist material comprises the following steps:

[0059] (1) 2-Fluorobenzoic acid (3.23 g, 23 mmol) and 3-methylbenzoic acid (3.12 g, 23 mmol) were dissolved in 51 mL of acetonitrile to form solution A;

[0060] (2) dissolving 1.6 mL of isopropyl titanate in 10.2 mL of acetonitrile to form solution B;

[0061] (3) Solution A was transferred to solution B, and the mixture was stirred evenly, and then transferred to a 100 mL polytetrafluoroethylene-lined reactor and placed in an oven for solvothermal reaction. The heating temperature was set to 100 °C and the reaction time was 15 h. After the heating reaction was completed, it was naturally cooled to room temperature. After filtering, washing, and drying, a fluorine-containing titanium oxide nanoparticle photoresist material was obtained. According to the test results of nuclear magnetic hydrogen spectrum, it was named F-BA-m-TA-Ti 1 / 1 according to the molar ratio of 2-fluorobenzoic acid and 3-methylbenzoic acid in the actual product.

[0062] Example 5

[0063] A method for preparing a fluorine-containing titanium oxide nanoparticle photoresist material comprises the following steps:

[0064] (1) 3-Fluorobenzoic acid (3.23 g, 23 mmol) and 3-methylbenzoic acid (3.12 g, 23 mmol) were dissolved in 51 mL of acetonitrile to form solution A;

[0065] (2) dissolving 1.6 mL of isopropyl titanate in 10.2 mL of acetonitrile to form solution B;

[0066] (3) Solution A was transferred to solution B, and after mixing and stirring evenly, the mixture was transferred to a 100 mL polytetrafluoroethylene-lined reactor and placed in an oven for solvent thermal reaction. The heating temperature was set to 100 °C and the reaction time was 15 h. After the heating reaction was completed, the mixture was naturally cooled to room temperature. After filtering, washing, and drying, a fluorine-containing titanium oxide nanoparticle photoresist material was obtained, which was named F-BA-m-TA-Ti-1.

[0067] Example 6

[0068] A photoresist composition comprises the following components by mass: 97.8 parts of solvent cyclopentanone, 2 parts of fluorine-containing titanium oxide nanoparticle photoresist material (F-BA-BA-Ti 1 / 1.35) prepared by the method of Example 1, and 0.2 parts of photoacid NIT.

[0069] Preparation of photoresist composition:

[0070] F-BA-BA-Ti 1 / 1.35 and photoacid NIT are dissolved in cyclopentanone solvent, and filtered through a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm to obtain a photoresist solution, namely a photoresist composition.

[0071] Preparation of photoresist film:

[0072] A 2-inch silicon wafer was adsorbed on a spin coater, and the photoresist composition obtained above was spin-coated at a rotation speed of 2000 rpm / min for 60 seconds, and then baked on a hot plate at 80° C. for 1 minute to obtain a photoresist film.

[0073] Example 7

[0074] A photoresist composition comprises the following components by mass: 97.8 parts of solvent cyclopentanone, 2 parts of fluorine-containing titanium oxide nanoparticle photoresist material (F-BA-BA-Ti 1 / 0.78) prepared by the method of Example 2, and 0.2 parts of photoacid NIT.

[0075] Preparation of photoresist composition:

[0076] F-BA-BA-Ti 1 / 0.78 and photoacid NIT were dissolved in cyclopentanone solvent, and filtered through a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm to obtain a photoresist solution, namely, a photoresist composition.

[0077] Preparation of photoresist film:

[0078] A 2-inch silicon wafer was adsorbed on a spin coater, and the photoresist composition obtained above was spin-coated at a rotation speed of 2000 rpm / min for 60 seconds, and then baked on a hot plate at 80° C. for 1 minute to obtain a photoresist film.

[0079] Example 8

[0080] A photoresist composition comprises the following components by mass: 97.8 parts of solvent cyclopentanone, 2 parts of fluorine-containing titanium oxide nanoparticle photoresist material (F-BA-m-TA-Ti 1 / 1.19) prepared by the method of Example 3, and 0.2 parts of photoacid NIT.

[0081] Preparation of photoresist composition:

[0082] F-BA-m-TA-Ti 1 / 1.19 and photoacid NIT were dissolved in cyclopentanone solvent and filtered through a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm to obtain a photoresist solution, namely, a photoresist composition.

[0083] Preparation of photoresist film:

[0084] A 2-inch silicon wafer was adsorbed on a spin coater, and the photoresist composition obtained above was spin-coated at a rotation speed of 2000 rpm / min for 60 seconds, and then baked on a hot plate at 80° C. for 1 minute to obtain a photoresist film.

[0085] Example 9

[0086] A photoresist composition comprises the following components by mass: 97.8 parts of solvent cyclopentanone, 2 parts of fluorine-containing titanium oxide nanoparticle photoresist material (F-BA-m-TA-Ti 1 / 1) prepared by the method of Example 4, and 0.2 parts of photoacid NIT.

[0087] Preparation of photoresist composition:

[0088] F-BA-m-TA-Ti 1 / 1 and photoacid NIT are dissolved in cyclopentanone solvent, and filtered through a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm to obtain a photoresist solution, namely a photoresist composition.

[0089] Preparation of photoresist film:

[0090] A 2-inch silicon wafer was adsorbed on a spin coater, and the photoresist composition obtained above was spin-coated at a rotation speed of 2000 rpm / min for 60 seconds, and then baked on a hot plate at 80° C. for 1 minute to obtain a photoresist film.

[0091] Example 10

[0092] A photoresist composition comprises the following components by mass: 97.8 parts of solvent cyclopentanone, 2 parts of fluorine-containing titanium oxide nanoparticle photoresist material (F-BA-m-TA-Ti-1) prepared by the method of Example 5, and 0.2 parts of photoacid NIT.

[0093] Preparation of photoresist composition:

[0094] F-BA-m-TA-Ti-1 and photoacid NIT are dissolved in cyclopentanone solvent and filtered through a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm to obtain a photoresist solution, i.e., a photoresist composition.

[0095] Preparation of photoresist film:

[0096] A 2-inch silicon wafer was adsorbed on a spin coater, and the photoresist composition obtained above was spin-coated at a rotation speed of 2000 rpm / min for 60 seconds, and then baked on a hot plate at 80° C. for 1 minute to obtain a photoresist film.

[0097] Comparative Example 1

[0098] A method for preparing a photoresist material comprises the steps of:

[0099] (1) Dissolve benzoic acid (5.67 g, 46 mmol) in 51 mL of acetonitrile to form solution A;

[0100] (2) dissolving 1.6 mL of isopropyl titanate in 10.2 mL of acetonitrile to form solution B;

[0101] (3) Solution A was transferred to solution B, and after mixing and stirring, the mixture was transferred to a 100 mL polytetrafluoroethylene-lined reactor and placed in an oven for solvent thermal reaction. The heating temperature was set to 100° C. and the reaction time was 15 h. After the heating reaction was completed, the mixture was naturally cooled to room temperature, and the photoresist material I was obtained by filtering, washing, and drying.

[0102] Comparative Example 2

[0103] A method for preparing a photoresist material comprises the steps of:

[0104] (1) 3-Methylbenzoic acid (6.26 g, 46 mmol) was dissolved in 51 mL of acetonitrile to form solution A;

[0105] (2) dissolving 1.6 mL of isopropyl titanate in 10.2 mL of acetonitrile to form solution B;

[0106] (3) Solution A was transferred to solution B, and after mixing and stirring, the mixture was transferred to a 100 mL polytetrafluoroethylene-lined reactor and placed in an oven for solvent thermal reaction. The heating temperature was set to 100° C. and the reaction time was 15 h. After the heating reaction was completed, the mixture was naturally cooled to room temperature, and photoresist material II was obtained after filtering, washing, and drying.

[0107] Comparative Example 3

[0108] A photoresist composition comprises the following components by mass: 97.8 parts of solvent cyclopentanone, 2 parts of photoresist material I prepared by the method of comparative example 1, and 0.2 parts of photoacid NIT.

[0109] Preparation of photoresist composition:

[0110] The photoresist material I and the photoacid NIT are dissolved in a cyclopentanone solvent, and filtered through a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm to obtain a photoresist solution, namely, a photoresist composition.

[0111] Preparation of photoresist film:

[0112] A 2-inch silicon wafer was adsorbed on a spin coater, and the photoresist composition obtained above was spin-coated at a rotation speed of 2000 rpm / min for 60 seconds, and then baked on a hot plate at 80° C. for 1 minute to obtain a photoresist film.

[0113] Comparative Example 4

[0114] A photoresist composition comprises the following components by mass: 97.8 parts of solvent cyclopentanone, 2 parts of photoresist material II prepared by the method of comparative example 2, and 0.2 parts of photoacid NIT.

[0115] Preparation of photoresist composition:

[0116] The photoresist material II and the photoacid NIT are dissolved in a cyclopentanone solvent, and filtered through a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm to obtain a photoresist solution, namely, a photoresist composition.

[0117] Preparation of photoresist film:

[0118] A 2-inch silicon wafer was adsorbed on a spin coater, and the photoresist composition obtained above was spin-coated at a rotation speed of 2000 rpm / min for 60 seconds, and then baked on a hot plate at 80° C. for 1 minute to obtain a photoresist film.

[0119] Test Example 1

[0120] The product of Example 1-2 was subjected to H-NMR spectrum analysis.

[0121] H NMR spectrum analysis (Switzerland, model: Bruker Avance Digital 400MHz): The products of Examples 1-2 were dissolved in deuterated dimethyl sulfoxide and subjected to H NMR spectrum testing. The H NMR spectrum results are as follows: Figure 1 As shown, the results demonstrated the successful introduction of 2-fluorobenzoic acid and benzoic acid ligands.

[0122] Test Example 2

[0123] The products of Example 3-4 were analyzed by H NMR spectrum under the same test conditions as in Experimental Example 1. Figure 2 As shown, the results demonstrated the successful introduction of 2-fluorobenzoic acid and 3-methylbenzoic acid ligands.

[0124] Test Example 3

[0125] The products of Examples 2 and 4 were subjected to thermal analysis.

[0126] Thermal analysis (NETZSCH, model STA449F3): In an argon environment, the temperature was raised from room temperature to 600°C at a rate of 10°C / min. The obtained thermal analysis curve is as follows Figure 3 As shown in the figure, it can be seen that the two titanium-based nanoparticle photoresists have high thermal stability, and the weight loss before 200°C originates from the unreacted raw materials in the material.

[0127] Test Example 4

[0128] The products F-BA-BA-Ti 1 / 1.35 and F-BA-BA-Ti 1 / 0.78 of Example 1-2 were subjected to particle size analysis.

[0129] Dynamic light scattering instrument (Anton Paar, model: Litesizer 500): The photoresist solution was prepared with cyclopentanone as solvent. The obtained particle size distribution curve is as follows Figure 4 As shown in the figure, it can be seen that the average particle size of F-BA-BA-Ti 1 / 1.35 and F-BA-BA-Ti 1 / 0.78 is small and evenly distributed, and the average size is mainly concentrated in 9nm.

[0130] Test Example 5

[0131] The products F-BA-m-TA-Ti 1 / 1.19 and F-BA-m-TA-Ti 1 / 1 of Example 3-4 were subjected to particle size analysis.

[0132] The particle size was measured under the same test conditions as in Experiment 4. The obtained particle size distribution curve is shown in Figure 5 As shown in the figure, it can be seen that the average particle size of F-BA-m-TA-Ti 1 / 1.19 and F-BA-m-TA-Ti 1 / 1 is small and evenly distributed, and the average size is mainly concentrated between 8nm.

[0133] Test Example 6

[0134] In order to evaluate the quality of the photoresist films spin-coated in Examples 6-9, the surface morphology of the photoresist films was collected using an atomic force microscope (AFM) (Shimadzu, model: SPM-9700HT) in touch mode, with the collection area set to 10 μm*10 μm. The surface morphology of the photoresist films of Examples 6-9 observed by AFM is shown in FIG. Figure 6 As shown, the measured root mean square roughness (Rq) of the films are 0.50nm, 0.50nm, 0.40nm and 0.57nm, respectively, indicating that the surface is flat and smooth and the film quality is good.

[0135] Test Example 7

[0136] Electron beam exposure experiment: The photoresist films of Examples 6-9 were exposed using electron beam lithography (e-beam lithography; EBL) (Germany, Pioneer Two, Raith GmbH), with a voltage of 30 kV and an aperture of 10 mm. The exposed silicon wafers were immediately developed in butyl lactate for 30 seconds and dried with nitrogen. The developer can also be cyclopentanone, ethyl lactate, ethyl acetate, toluene. The design line width is less than 50 nm.

[0137] The above lithographic patterns were characterized using the scanning electron microscope imaging function of the electron beam lithography system, such as Figure 7 As shown in Tables 1 and 2, the minimum line widths that can be achieved by the photoresist films prepared in Examples 6-9 are 13nm, 11nm, 12nm, and 16nm, respectively, and the line width roughness range of the obtained line width is 1-3nm, which proves that the fluorine-containing titanium oxide nanoparticle photoresist has good lithography performance.

[0138] Test Example 8

[0139] In order to prove that the fluorinated ligand improves the imaging quality of the titanium oxide nanoparticle photoresist, the photoresist film of Comparative Example 3-4 was exposed using electron beam lithography (e-beam lithography; EBL) (Germany, Pioneer Two, Raith GmbH), with a voltage of 30 kV and an aperture of 10 mm. The exposed silicon wafer was immediately developed in butyl lactate for 30 seconds and dried with nitrogen. The developer can also be cyclopentanone, ethyl lactate, ethyl acetate, toluene. The design line width is less than 50 nm.

[0140] The above lithographic patterns were characterized using the scanning electron microscope imaging function of the electron beam lithography system, such as Figure 8-9 As shown in Tables 1 and 2, the minimum line widths that can be achieved by the photoresist films of Comparative Examples 3-4 are 18 nm and 21 nm, and the line width roughness of the line width that can be obtained is in the range of 2-5 nm. Compared with the results obtained by the fluorine-containing photoresist films of Examples 7 and 9, the fluorine-free photoresist films of Comparative Examples 3-4 require a higher exposure dose to obtain a straight line of the same line width under electron beam exposure, have a lower sensitivity, and have a larger line width roughness (LWR), proving that the introduction of fluorine-containing ligands can improve the sensitivity of titanium oxide nanoparticle photoresists and reduce line width roughness (LWR), improve imaging quality, and have excellent lithography performance.

[0141] Table 1. Line width and line width roughness (LWR) of the photoresist films of Example 7 and Comparative Example 3 at different exposure doses (designed line width of 50nm-20nm, line width / spacing of 1 / 5).

[0142]

[0143] Table 2. Line width and line width roughness (LWR) of the photoresist films of Example 9 and Comparative Example 4 at different exposure doses (designed line width of 50nm-20nm, line width / spacing of 1 / 5).

[0144]

Claims

1. A method for preparing a fluorine-containing titanium oxide nanoparticle photoresist material, comprising the steps of: (1) dissolving a fluorine-containing ligand and a non-fluorine-containing ligand in a solvent A to obtain a solution A; (2) dissolving a titanium source in solvent B to obtain solution B; (3) Solution A and solution B are fully mixed, subjected to solvent thermal reaction, and then filtered, washed, and dried to obtain a fluorine-containing titanium oxide nanoparticle photoresist material.

2. The method for preparing the fluorine-containing titanium oxide nanoparticle photoresist material according to claim 1, characterized in that: In step (1), the fluorine-containing ligand is one or a combination of two or more of 2-fluorobenzoic acid, 3-fluorobenzoic acid, 4-fluorobenzoic acid, 2,3-difluorobenzoic acid, 2,4-difluorobenzoic acid, 2,5-difluorobenzoic acid, 2,6-difluorobenzoic acid, 3,4-difluorobenzoic acid, 2,4,5-trifluorobenzoic acid, 2,4,6-trifluorobenzoic acid, 3-fluoro-2-(trifluoromethyl)benzoic acid, 2-fluorophenylacetic acid, 2,4,5-trifluorophenylacetic acid or 2-(trifluoromethyl)acrylic acid; preferably, the fluorine-containing ligand is 2-fluorobenzoic acid.

3. The method for preparing the fluorine-containing titanium oxide nanoparticle photoresist material according to claim 1, characterized in that: In step (1), the non-fluorinated ligand is one or a combination of two or more of benzoic acid, 2-methylbenzoic acid, 3-methylbenzoic acid, 4-methylbenzoic acid, 4-aminobenzoic acid, 4-hydroxybenzoic acid, 2-methylphenylacetic acid, 3-methylphenylacetic acid, 4-methylphenylacetic acid or methacrylic acid.

4. The method for preparing the fluorine-containing titanium oxide nanoparticle photoresist material according to claim 1, characterized in that: In step (1), the molar ratio of the fluorine-containing ligand to the non-fluorine-containing ligand is 1:0.5-1:4, preferably 1:1-1:3.

6.

5. The method for preparing the fluorine-containing titanium oxide nanoparticle photoresist material according to claim 1, characterized in that: Includes one or more of the following conditions: i. In step (1), solvent A is one of acetonitrile, ethyl acetate, n-hexane or n-heptane; the volume ratio of the molar amount of the fluorinated ligand to solvent A is 0.1-0.5 mol / L; ii. In step (2), the titanium source is one of isopropyl titanate or tetrabutyl titanate; iii. In step (2), solvent B is one of acetonitrile, ethyl acetate, n-hexane or n-heptane; the volume ratio of the titanium source to solvent B is 1:6-7; iv. The volume ratio of the molar amount of the fluorinated ligand in solution A of step (1) to the volume ratio of the titanium source in solution B of step (2) is 6-15 mol:1L; v. In step (3), the reaction temperature is 60-100°C; the reaction time is 15-24h.

6. A fluorine-containing titanium oxide nanoparticle photoresist material, characterized in that: Obtained by the method according to any one of claims 1 to 5.

7. The fluorine-containing titanium oxide nanoparticle photoresist material according to claim 6, characterized in that: The microscopic morphology of the fluorine-containing titanium oxide nanoparticle photoresist material is nanoparticles with a particle size of 3-11 nm.

8. A photoresist composition, characterized in that The composition comprises the following components by weight: 50-99 parts of solvent, 1-50 parts of fluorine-containing titanium oxide nanoparticle photoresist material, and 0-10 parts of photoacid; Preferably, the solvent is selected from one or a combination of two or more of cyclopentanone, cyclohexanone, acetone, propylene glycol methyl ether acetate, ethyl lactate, butyl lactate, toluene, dimethyl sulfoxide or tetrahydrofuran; preferably, the solvent is cyclopentanone; Preferably, the photoacid is selected from N-hydroxynaphthalimide trifluoromethanesulfonic acid (NIT), 2-(2-(((octylsulfonyl)oxy)imino)thiophen-3(2H)-ylidene)-2-(o-tolyl)acetonitrile (PAG 108) or N-hydroxyphthalimide p-toluenesulfonate.

9. The method for preparing the photoresist composition as claimed in claim 8, comprising the steps of: fully dispersing the fluorine-containing titanium oxide nanoparticle photoresist material and the photoacid in a solvent to obtain the photoresist composition.

10. Use of the fluorine-containing titanium oxide nanoparticle photoresist material or photoresist composition according to claim 6 or 8 in photolithography technology.